Topology optimization of transient thermo-mechanical problems using multiple materials - Günther-Hanssen,Olov (ISRN LUTFD2/TFHF-20/TFHF-5239-SE(1-67), 2020)
Topology optimization is a powerful method for finding optimized designs for a variety of problems. In this work, thermo-mechanical problems are studied in particular and solved under transient conductive heat transfer using 2 materials plus void in the optimization. In the first part of the thesis, the theoretical background for a generic transient thermo-mechanical topology optimization problem is introduced. The thermo-mechanical field is modeled using have a one-way coupling between the temperature field to the displacement field and is solved with the Finite Element Method for small deformations. To render designs with a minimal length scale and clear boundaries, design filtering is used together with a robust formulation, which is reliant on Heaviside projections. The second part goes more into the details of the implementation in Matlab and the test cases used as well as a real-world application: optimizing a thermally actuated disassembly mechanism. The results are verified against external previous results and are similar in the features. The optimal design for the real-world application is from a topology optimization perspective satisfactory but shows very small displacements under the thermal load. As future work, large deformations are suggested to be implemented.
Keywords: topology optimization; transient heat transfer; multi-material; thermal actuators